Doing the right thing with water: combining market-based principles with policy intervention for the sustainable management of water in agriculture - Msangi, Siwa; Ringler, Claudia; Rosegrant, Mark W. (CAB International, 2006)
The increasing importance of sustainability in natural resource management is drawing increasing attention, worldwide, to the role that policies can play in enhancing the management and allocative efficiency of water. Looking at various examples from the literature, we discuss some best practices that have been applied in a variety of empirical settings, while highlighting some of the pitfalls to avoid. We discuss the role that assigning water rights can play in creating the necessary incentives for market-based mechanisms of re-allocation to work for water management. We also emphasize the role that remains for centralized regulatory authority, and the need for collective action to ensure that essential ecosystem requirements are met. Among the variety of examples cited are those of inter-sectoral transfers, conjunctive use of surface and groundwater and tradable permit mechanisms for which we also highlight the enabling institutional requirements.